Foreign Grant Support for Projects in the Context of R&D Structure and Performance in Ukraine - Malitsky, B.A. (Наука та наукознавство, 2015)
Information about peculiarities and trends of grant form of R&D financing in Ukraine is given. It is emphasized that it was developing in Ukraine along with rapid decline in R&D financing, which entailed mainly “utilitarian” view of foreign grants, although they should be regarded as, first and foremost, as an effective means for internationalization of the national R&D system. Main reasons for intensification of grant form of foreign support to national R&D are highlighted. Factors determining participation of Ukrainian researchers in international projects with grant financing are outlined: the performance of domestic research potential and the thematic conformity of R&D conducted in Ukraine and beyond Ukraine. Estimates on publication activity of Ukrainian researchers, derived using domestic and international databases, and results of a comparative analysis of the publication activity of researchers from Ukraine and selected European countries are given. The problem of grant R&D financing inside Ukraine is discussed.